#### Answer

$g(-1)=-8$
$f(g(-1))=76$

#### Work Step by Step

Put x=1 for the g(x) function.
$g(-1)=3(-1)-5=-8$
Then put x=-8 for the f(x) function.
$f(g(-1))=f(-8)=(-8)^{2}-(-8)+4=64+8+4=76$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$g(-1)=-8$
$f(g(-1))=76$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.